2009
DOI: 10.1002/joc.1970
|View full text |Cite
|
Sign up to set email alerts
|

Land‐ocean contrasts in lightning activity over the Indian region

Abstract: Land-ocean contrasts in the lightning activity over Indian land and two surrounding oceanic regions viz. Arabian Sea and Bay of Bengal have been studied. Satellite-based lightning flash data for 5-year (1998-2002) period have been used. The study revealed that lightning activity over Bay of Bengal was three times higher than that over Arabian Sea and 9.3 times lower than that over land. The bimodal distribution is seen over Arabian Sea (peaks in April and November), and land (peaks in May and September). A un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 67 publications
(81 reference statements)
2
4
0
Order By: Relevance
“…The above findings depict that land manifests higher FCPD than ocean but for lower FCPD the frequency is higher over ocean. This finding reconfirms the observation of Kandalgaonkar et al (2010).…”
Section: Resultssupporting
confidence: 94%
“…The above findings depict that land manifests higher FCPD than ocean but for lower FCPD the frequency is higher over ocean. This finding reconfirms the observation of Kandalgaonkar et al (2010).…”
Section: Resultssupporting
confidence: 94%
“…Thus, the higher magnitude of the lightning activity over the BoB compared with that over the AS may be attributed to an increase in convection because of higher SSTs. These results are in agreement with previous studies (Kandalgaonkar et al, 2002(Kandalgaonkar et al, , 2010.…”
Section: Data and Source Descriptionsupporting
confidence: 96%
“…Their study showed that the highest SSTs occurred over the BoB in May to June and the lowest in December. Convection over the oceans depends primarily on SSTs (Kandalgaonkar, Kulkarni, Tinmaker, & Kulkarni, 2010). Thus, the higher magnitude of the lightning activity over the BoB compared with that over the AS may be attributed to an increase in convection because of higher SSTs.…”
Section: Data and Source Descriptionmentioning
confidence: 97%
“…These studies significantly add not only in understanding the spatio‐temporal variability of lightning activity in particular area of investigation (Lal and Pawar, 2009; Ramesh Kumar and Kamra, 2010; Tinmaker et al ., 2010, 2014, 2015; Tinmaker and Ali, 2012; Siingh et al ., 2014; Lal et al ., 2018; Mushtaq et al ., 2018) but also over the whole Indian region (Kandalgaonkar et al ., 2003; Kandalgaonkar et al ., 2005; Yoshida et al ., 2007, Ranalkar and Chaudhari (2009); Murugavel et al ., 2014; Chate et al ., 2017; Nath et al ., 2009; Tinmaker et al ., 2019). In addition, these studies deal with some particular features such as the land‐ocean contrast (Nath et al ., 2009; Kandalgaonkar et al ., 2010a; Kandalgaonkar et al ., 2010b; Chate et al ., 2017), asymmetry in eastern and western parts of India (Nath et al ., 2009; Tinmaker and Chate, 2013), effect of El‐Nino and La‐Nina events (Siingh et al ., 2017; Saha et al ., 2017a; Tinmaker et al ., 2017a, 2017b; Saha et al ., 2017b) on the lightning activity and its temporal distribution in tropical cyclones over north Indian Ocean (Ranalkar et al ., 2017). Most of these localized case studies suggest that a relationship exists between the lightning flash rate and meteorological parameters, which govern the formation and development of storms.…”
Section: Introductionmentioning
confidence: 99%